Richard Scarry's best sing-along Mother Goose video ever! - Scarry, Richard; Eastman, Tony; Weiss, Ellen; DeRose, Rich (Sony Wonder, 2002)
Huckle looks for his friend Lowly Worm through Mother Gooseland and meets many new friends. Sing along with classic nursey rhymes.